Highly oxygenated cyclohexenes from the leaves of Uvaria grandiflora Roxb. ex Hornem and their cytotoxic and α-glucosidase inhibitory activities - Virayu Suthiphasilp; Moses Egoh Betangah; Passakorn Teerapongpisan; Narawadee Rujanapun; Boonyanoot Chaiyosang; Sarawut Tontapha; Pakit Kumboonma; Brian O. Patrick; Raymond J. Andersen; Rawiwan Charoensup; Thidarat Duangyod; Phunrawie Promnart; et al. (Heliyon)
Phytochemical investigation of the leaf extract of Uvaria grandiflora Roxb. ex Hornem led to the isolation and identification of two new highly oxygenated cyclohexenes, uvariagrandols A (1) and B (2), together with seven known compounds (3–9). Their structures were elucidated by spectroscopic methods as well as comparisons made from the literature. The (1S,2S,3R,6S) absolute configuration of uvariagrandols A and B was established by the comparison of the experimental and calculated electronic circular dichroism (ECD). (+)-Grandifloracin (9) displayed cytotoxicity against SW480 and K562 cell lines with IC50 values of 154.9 and 60.9 μM, respectively. 6-Methoxyzeylenol (5) had α-glucosidase inhibitory activity with the IC50 value of 34.1 μM.